The EVALUASI KESESUAIAN LAHAN UNTUK PENGEMBANGAN TANAMAN REMPAH UTAMA DI DESA CUKILAN, KECAMATAN SURUH, KABUPATEN SEMARANG - Celine Vera Feronica; Andree Wijaya Setiawan (Jurnal Tanah dan Sumberdaya Lahan, 2023)
The availability of information regarding the cultivation of spice plants is still limited, so studies are needed to support the development of spice plants. This study aimed to identify land characteristics, land suitability classes and distribution maps, limiting factors and recommendations for the development of spice cultivation. The analytical method used was Location Quotient (LQ), and Shift Share Analysis (SSA) to determine the main spice commodities. Overlay and matching between land characteristic parameters and land suitability criteria through ArcGis software version 10.4. The results of the study obtained two main commodities, namely cardamom, with an LQ of 1.98 and ginger, with an LQ of 1.05. Land suitability classes for cardamon are quite suitable (S2), covering an area of 583.89 ha (94.1%) and marginally suitable (S3), covering an area of 36.87 ha (5.9%) with drainage limiting factors, rainfall, base saturation, slope, CEC, pH, and organic C. Land suitability classes for ginger are moderately suitable (S2) with a land area of 541.71 ha (87.3%) and marginally suitable marginal (S3) covering an area of 79.06 ha (12.7%) with the limiting factors of rainfall, temperature, drainage, slope, base saturation, salinity, CEC, pH, and organic C.